Fragilidade hídrica e ecodinâmica na bacia hidrográfica do rio Sergipe : desafios à gestão das águas - Silva, Luiz Carlos Sousa (2014)
The river basin as a geo-environmental unit of study is an important scenario for the knowledge of the functioning of the natural resources and consequent efficient and balanced planning of its usage, in order to adapting to the particular characteristics and capabilities of each environment. The Sergipe River Basin (SRB), for its peculiarities and economic, social and cultural importance to the State of Sergipe, was chosen as stage for our analysis focused on an integrated study that provides reliable subsidies for the elaboration of conservation policies and better use of the natural resources, more precisely, water. Being one of the most anthropized of the State because in its area there are important cities from an economic and population point of view, e.g. Aracaju, Nossa Senhora do Socorro, Itabaiana and Nossa Senhora da Glória, the study of the SRB, under the perspective proposed in this work, aims to bring contributions that may serve as a basis for further studies. The objective of this work is to analyze the ecodynamic water fragility in physiographic environments of the Sergipe River Basin, through assessing its water potential, conflicts generated from the multiple uses of water and the management model established by the Water Law. The methodological approach chosen for the analysis was based on the literature review of authors who treat the theme in question, by assessing, through the geo-environmental frailty model, which was developed by Ross (1994), the conditions of fragility of the basin. Previous researches have indicated that the Sergipe River Basin presents intense geo-environmental fragility, with its soils, waters, vegetation coverage and micro climates in constant exposure to the ecodynamics instability conditions caused by anthropic actions everywhere at the SRB, mainly due to the way of ownership and use of natural areas and water resources. The different geo-environmental peculiarities in each section of the BHS suggest different results of ecodynamic potential fragility and ecodynamic emerging fragility, thus contributing to the ecodynamic water weakness in the SRB ecodynamics with strong evidences of shortage and dependence of water from other water basins. This fragility on the water environment is governed by the model of use and occupation of soil in the twenty-six counties of the SRB. This finding reinforces the thesis that, by the peculiar and particular characteristics of each physiographic environment present in the Sergipe River Basin, the change and the adequacy of current management model need to be, urgently, implemented to answer the individual characteristics of each environments that make up the water basin of the Sergipe river, to strengthen the management of water resources and ensure water, quality and quantitatively, throughout the Sergipe River Basin to the multiple uses of present and future generations.